Mutu Lembaga Pendidikan Islam: Tantangan dan Harapan - Marintang Marintang; La Tamsir Siompo; Muliani Muliani; Sukma Nurmaula; Mardiah Hasan; Muhammad Ramli (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to examine the concept of quality in Islamic educational institutions, identify the main challenges faced in improving quality, and formulate strategic expectations for developing quality in the era of globalization and digitalization. This study uses a qualitative approach with a library research method. Data were collected from various secondary sources, such as scientific journals, books, and relevant research, which were then analyzed using content analysis techniques. The findings show that quality in Islamic education is not only oriented towards academic and managerial achievement based on Total Quality Management (TQM) principles, but is also deeply rooted in the Islamic values of ihsan and itqan. The main challenges include limited human resource competence, inadequate infrastructure, financing constraints, and the pressure of digital transformation. To overcome these challenges, a sustainable development strategy is formulated, which includes strengthening vision-driven leadership, continuously developing teacher professionalism, implementing integrated quality management, digital transformation, and optimizing community partnership.